A Granular Physics‐Based View of Fault Friction Experiments. Issue 6 (25th June 2020) - Ferdowsi, Behrooz; Rubin, Allan M.
Abstract: Rate‐ and state‐dependent friction (RSF) equations are commonly used to describe the time‐dependent frictional response of fault gouge to perturbations in sliding velocity. Among the better‐known versions are the Aging and Slip laws for the evolution of state. Although the Slip law is more successful, neither can predict all the robust features of lab data. RSF laws are also empirical, and their micromechanical origin is a matter of much debate. Here we use a granular physics‐based model to explore the extent to which RSF behavior, as observed in rock and gouge friction experiments, can be explained by the response of a granular gouge layer with time‐independent properties at the contact scale. We examine slip histories for which abundant lab data are available and find that the granular model (1) mimics the Slip law for those loading protocols where the Slip law accurately models laboratory data (velocity‐step and slide‐hold tests) and (2) deviates from the Slip law under conditions where the Slip law fails to match laboratory data (the reslide portions of slide‐hold‐slide tests), in the proper sense to better match those data. The simulations also indicate that state is sometimes decoupled from porosity in a way that is inconsistent with traditional interpretations of "state" in RSF. Finally, if the "granular temperature" of the gouge is suitably normalized by the confining pressure, it produces an estimate of the direct velocity effect (the RSF parameter a ) that is consistent with our simulations and in the ballpark of lab  data. Key Points: We examined the behavior of a sheared granular layer with time‐independent contact‐scale properties at and away from steady state Like gouge samples in the lab, the layer mimics the rate‐state friction Slip law in velocity‐step and slide‐hold (but not reslide) tests A normalized granular temperature can be used to estimate the amplitude of the direct velocity dependence of friction in the gouge layer